Valuable content marketing how to make quality content your key to success - Jefferson, Sonja; Tanton, Sharon (London Kogan Page, 2015)
"The first edition of Valuable Marketing Content provided a clear, straightforward guide on what to write and produce, what type of information to share, and how to share it to get the most effective results. Written for the current business environment, particularly start-ups and consulting companies, this updated second edition offers new ideas, examples, step-by-step action lists, quick tips, and goal-driven chapter summaries to help businesses create compelling, targeted content for their customers"--Provided by publisher.
"From websites, white papers and blogs to tweets, newsletters and video, content is king in the digital world, now more than ever. When businesses get it right and create the type of marketing people love they have a huge opportunity to connect with clients and customers in ways their customers appreciate, trust and want. Valuable Content Marketing shows how to create and share valuable content on websites and through social media and more traditional methods. This fully revised second edition of Valuable Content Marketing is a practical, focused guide to effective marketing. It includes new ideas and examples, step-by-step action lists, quick tips and goal-driven chapter summaries to make understanding the key concepts easier than ever. Perfect for sales, marketing and branding professionals as well as small business owners or practitioners in publicity or corporate communications, it provides inspiration from companies of all sizes that have got valuable content marketing right, from small companies like software development firm Desynit to household names like Accenture"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Marketing; Internet marketing; Customer relations